Comparison of the effectiveness and safety of insulin and oral hypoglycemic drugs in the treatment of gestational diabetes mellitus: a meta-analysis of 26 randomized controlled trials. (3rd April 2022) - Li, Chaolin; Gao, Can; Zhang, Xianqin; Zhang, Lin; Shi, Hao; Jia, Xu
Abstract: Objective: Oral hypoglycemic drugs for the treatment of gestational diabetes mellitus (GDM) are still controversial because they can pass through the placenta. The purpose of this meta-analysis is to evaluate the safety and effectiveness of oral hypoglycemic drugs. Methods: PubMed, Ovid Embase, Web of Science, and Cochrane databases were systematically searched (inception to 20 April 2021). Rev Man 5.0 was used to analyze the data. A random-effects model was used to compute the summary risk estimates. Results: There were 26 randomized controlled trials (RCTs) involving 4921 GDM patients which were included in this meta-analysis. Compared with metformin, insulin had a significant increase in the risk of preeclampsia (odds ratio [OR], 1.61; 95% confidence interval [CI], 1.06 to 2.45; I 2 =40%; p < .05), hypertension (OR, 1.42; 95% CI, 1.02 to 1.99; I 2 =0%; p < .05), hypoglycemia (OR, 3.93; 95% CI, 1.27 to 12.19; I 2 =0%; p < .05), neonatal hypoglycemia (OR, 1.92; 95% CI, 1.34 to 2.76; I 2 =41%; p < .0001), neonatal jaundice (OR, 2.70; 95% CI, 1.12 to 6.52; I 2 =0%; p < .05), and Neonatal Intensive Care Unit Admission (OR, 1.46; 95% CI, 1.09 to 1.95; I 2 =39%; p < .05), but the risk of neonatal macrosomia (OR, 1.67; 95% CI, 1.12 to 2.40; I 2 =0%; p < .05) and neonatal injury (OR, 0.70; 95% CI, 0.55 to 0.89; I 2 =0%; p < .01) is lower. Conclusions: Metformin is comparable with insulin in glycemic control and neonatal outcomes and has the potential to replace insulin therapy in clinical practice. Glyburide is behind metformin and insulin, and more RCTs are needed to verify its safety.